Upward migration of gas in an active tectonic basin: An example from the sea of Marmara. (July 2018) - Grall, Céline; Henry, Pierre; Dupré, Stéphanie; Géli, Louis; Scalabrin, Carla; Zitter, Tiphaine A.C.; Sengor, A.M.Celal; Namik Cagatay, M.; Cifci, Gunay
Abstract: Gases of various sources were collected at the seafloor of the Marmara basin suggesting that the gases expelled have experienced multiple sequences of upward migration, from multiple sources. The pathways of upward migration of gas can be reconstructed by considering the distribution of gas seeps with respect to the near-surface geomorphostructure and the regional stratigraphic architecture of the Marmara Basin. Gas seeps appear to be more favourably localized within a 1–2 km swath around active faults where sediment permeability is probably enhanced by deformation. In the fault zones, fault intersections between sets of transtensive and transpressive subsidiary faults, or between subsidiary faults and main faults, are the preferred gas pathways. These subsidiary structures localize methane seeps, observed as elongated black patches with bacterial mats, gas bubble emission sites, and chemoherms associated with buried mud volcanoes. Gas seeps are, however, rare along active faults segments crossing basin depocenters but focus along basin edges and along topographic highs. Considering the role of sedimentary layers as gas migration pathways can explain this characteristic of the distribution of gas seeps. Fault zones that cross updip gas migration pathways will vent comparatively more gas than fault zones on the downdip side. Moreover, gas accumulation and resulting overpressuring along the western fault segment crossing the Western High may be associated with aseismic fault creep and intense gas emissions at the seafloor. In contrast, the poorly focused seepage along the fault segment crossing the Central High may be linked to the locked state of this fault segment.